2017
DOI: 10.7567/jjap.56.115801
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of stretchable copper electrodes on poly(dimethylsiloxane) substrate by direct deposition

Abstract: Stretchable Cu electrodes are fabricated by direct deposition on He- and O2-plasma-treated and prestretched poly(dimethylsiloxane) (PDMS) substrates. The electrodes show conductivity owing to the formation of a hard and thin silica-like blocking layer, which forms low-period wavy structures on the PDMS substrate surface. The stretchable Cu electrode fabricated with He-plasma treatment shows superior performance compared with that fabricated with O2-plasma treatment under a strain condition owing to the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The stretching capability is a function of the mechanical properties of the compliant substrate and electrode, including metals and various hybrid metallic materials deposited or transferred onto the substrate. We previously reported that, because of Si-based process compatibility, direct deposition of metal electrodes such as Ag and Cu on a compliant substrate is the best way to realize high throughput and good stretching capability of poly dimethylsiloxane (PDMS) substrates [9,10]. To achieve low initial sheet resistance, it is important to block various types of impurities originating from the substrate, which have vast influence on metal electrodes on the compliant substrate realized by oxygen plasma or UV treatment, both of which form impurity blocking layers on the PDMS surface [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The stretching capability is a function of the mechanical properties of the compliant substrate and electrode, including metals and various hybrid metallic materials deposited or transferred onto the substrate. We previously reported that, because of Si-based process compatibility, direct deposition of metal electrodes such as Ag and Cu on a compliant substrate is the best way to realize high throughput and good stretching capability of poly dimethylsiloxane (PDMS) substrates [9,10]. To achieve low initial sheet resistance, it is important to block various types of impurities originating from the substrate, which have vast influence on metal electrodes on the compliant substrate realized by oxygen plasma or UV treatment, both of which form impurity blocking layers on the PDMS surface [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high stretching capability, the stretchable substrate is made with a carbon and oxygen compound, which leads to significant increases in the resistance of the electrodes, especially when metal electrodes are directly deposited on the stretchable substrate [7][8][9]. Minimizing the effect of the carbon and oxygen compound of the substrate is of importance in fabricating high-performance stretchable electrodes because they determine the performance of the stretchable electrodes in terms of the initial resistance, variation of resistance under strain conditions, and maximum stretching capability [10][11][12]. Therefore, careful choice of the electrode materials and surface treatments of the stretchable substrate are key factors in the fabrication of highperformance stretchable electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, strain sensors used to monitor heartbeat rate, face expression change, and phonation vibration have been rapidly developed in recent years. The stretchable conductors used in those sensors work via piezoresistive sensing mechanism, such as thin metal films (TMFs) deposited onto stretchable polymers and some filler‐type elastomers composed of carbon nanotubes, graphene, and metal nanowires . Particularly, TMFs strain sensors are feasible to be prepared in a large area by direct deposition approach, making it compatible with conventional Si‐based processes and easy to integrate into external circuits and devices.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, TMFs strain sensors are feasible to be prepared in a large area by direct deposition approach, making it compatible with conventional Si‐based processes and easy to integrate into external circuits and devices. However, the stiff feature of TMFs will lead to mechanical failure when stretched over their elongation limit, e.g., less than 1% for thin Cu films . To resolve this problem, various structures with wavy, buckle, wrinkle, or network topography have been introduced to adapt mechanical deformation .…”
Section: Introductionmentioning
confidence: 99%